PENGARUH KUALITAS LAYANAN, PERSEPSI HARGA, KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN (Studi Pada Cafe Punkgonane Pati) - Tjahjaningsih, Endang.; Ahmad Sofi’i, 13.05.51.0203 (Students' Journal of Economic and Management, 2018)
The purpose of this study is to determine the effect of service quality, nutrient perceptions, product quality to customer satisfaction cafe Punkgonane Pati.The population of this study is Punkgonane Pati cafe visitors. The sample 96 respondents with purposive sampling sampling method. Data were obtained by questionnaire. The variables of this study are service quality (X1), price perception (X2), product quality (X3), consumer satisfaction (Y).The results of this study indicate that the quality of service (X1), price perceptions (X2) and product quality (X3) indicate a positive and significant influence on customer satisfaction (Y)The conclusion of this research is quality of service (X1), perception of price (X2) and product quality (X3) shows positive and significant influence to customer satisfaction (Y). It is suggested to the chairman of the cafe Punkgonane Pati to improve the quality of service by providing training to employees. On the perception of the price should be the price of food and beverages offered at Punkgonane Pati cafe affordable to all consumers and the quality of Punkgonane Pati cafe products improve the delicious taste in every food and beverage served. Keywords : Service Quality, Price Perception, Product Quality and Consumer Satisfaction